2008
DOI: 10.1038/ng.2007.70
|View full text |Cite
|
Sign up to set email alerts
|

A single gene network accurately predicts phenotypic effects of gene perturbation in Caenorhabditis elegans

Abstract: The fundamental aim of genetics is to understand how an organism's phenotype is determined by its genotype, and implicit in this is predicting how changes in DNA sequence alter phenotypes. A single network covering all the genes of an organism might guide such predictions down to the level of individual cells and tissues. To validate this approach, we computationally generated a network covering most C. elegans genes and tested its predictive capacity. Connectivity within this network predicts essentiality, id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
338
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(345 citation statements)
references
References 49 publications
5
338
1
1
Order By: Relevance
“…In contrast, however, network theory predicts that weakly connected CR-upregulated genes will be less essential for survival. One approach for evaluating this prediction is to examine phenotypes of knock-out mice that lack CR-upregulated genes, or to examine the essentiality of orthologues in the S. cerevisiae, C. elegans and D. melanogaster model systems (Ekman et al, 2006;Lee et al, 2008). An important consideration is whether connectivity properties documented in this study are reflected at other levels of the interactome, such as metabolic and protein-protein interaction networks.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, however, network theory predicts that weakly connected CR-upregulated genes will be less essential for survival. One approach for evaluating this prediction is to examine phenotypes of knock-out mice that lack CR-upregulated genes, or to examine the essentiality of orthologues in the S. cerevisiae, C. elegans and D. melanogaster model systems (Ekman et al, 2006;Lee et al, 2008). An important consideration is whether connectivity properties documented in this study are reflected at other levels of the interactome, such as metabolic and protein-protein interaction networks.…”
Section: Discussionmentioning
confidence: 99%
“…We also used past C. elegans genome‐wide known and predicted gene product functional interactions from published meta‐analyses,35, 36, 37 as well human kinome‐wide known gene product functional interaction data from a published meta‐analysis, to construct potential functional networks for the kinases identified in each screen. The physical networks are based upon binding data (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The physical networks are based upon binding data (e.g. yeast two hybrid, co‐immunoprecipitation) for the C. elegans kinase and/or data for the yeast, fly, rodent, and/or human orthologue35, 36, 37 while the functional networks are based upon limited genetic interactions for the C. elegans kinase and/or data for the yeast, fly, rodent, and/or human orthologue35, 36, 37 and a large amount of biochemical data for shared interacting phospho‐proteins for the human orthologue 27. Visualization of these predicted interactions using cytoscape did indeed reveal some potential interaction networks (see Supporting Information [Link], [Link]).…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary Fig. 2), Ce-vap-1 is inferred to interact with 17 Ce-scl paralogs (Lee et al, 2008). Various experiments have also shown that Ce-scl-1 interacts (directly) with daf-2, daf-16 and age-1 (Larsen, 2003;Libina et al, 2003;Ookuma et al, 2003;Patterson, 2003;Liu et al, 2004;Zhong and Sternberg, 2006;Harada et al, 2007).…”
Section: Double-domain Proteinsmentioning
confidence: 99%
“…Ce-scl-5, the C. elegans ortholog of Hc-cap-14, encodes an extracellular CAP protein; the Ce-scl-5 gene is predicted to interact directly with Ce-vap-1 and Ce-vap-2 as well as a transcription factor enhancer encoded by the orphan gene F47B8.2 (Lee et al, 2008). Although its function is presently unknown, abundant transcription of Hc-cap-14 in parasitic stages of H. contortus indicates a role in parasitism or the host-parasite interplay.…”
Section: Single-domain Proteinsmentioning
confidence: 99%